An experimental subunit vaccine based on Bluetongue virus 4 VP2 protein fused to an antigen-presenting cells single chain antibody elicits cellular and humoral immune responses in cattle, guinea pigs and IFNAR(−/−) mice. Issue 22 (21st May 2015) - Legisa, D.M.; Perez Aguirreburualde, M.S.; Gonzalez, F.N.; Marin-Lopez, A.; Ruiz, V.; Wigdorovitz, A.; Martinez-Escribano, J.A.; Ortego, J.; Dus Santos, M.J.
Abstract: Bluetongue virus (BTV), the causative agent of bluetongue disease (BT) in domestic and wild ruminants, is worldwide distributed. A total of 27 serotypes have been described so far, and several outbreaks have been reported. Vaccination is critical for controlling the spread of BTV. In the last years, subunit vaccines, viral vector vaccines and reverse genetic-based vaccines have emerged as new alternatives to conventional ones. In this study, we developed an experimental subunit vaccine against BTV4, with the benefit of targeting the recombinant protein to antigen-presenting cells. The VP2 protein from an Argentine BTV4 isolate was expressed alone or fused to the antigen presenting cell homing (APCH) molecule, in the baculovirus insect cell expression system. The immunogenicity of both proteins was evaluated in guinea pigs and cattle. Titers of specific neutralizing antibodies in guinea pigs and cattle immunized with VP2 or APCH-VP2 were high and similar to those induced by a conventional inactivated vaccine. The immunogenicity of recombinant proteins was further studied in the IFNAR(−/−) mouse model where the fusion of VP2 to APCH enhanced the cellular immune response and the neutralizing activity induced by VP2.